The Transmission Electron Microscope Theory and Applications - Maaz, Khan (IntechOpen, 2015)
This book The Transmission Electron Microscope abundantly illustrates necessary insight and guidance of this powerful and versatile material characterization technique with complete figures and thorough explanations. The second edition of the book presents deep understanding of new techniques from introduction to advance levels, covering in-situ transmission electron microscopy, electron and focused ion beam microscopy, and biological diagnostic through TEM. The chapters cover all major aspects of transmission electron microscopy and their uses in material characterization with special emphasis on both the theoretical and experimental aspects of modern electron microscopy techniques. It is believed that this book will provide a solid foundation of electron microscopy to the students, scientists, and engineers working in the field of material science and condensed matter physics.